Pengembangan dan Pengujian Kelayakan Sistem Informasi Monitoring Inventaris Sekolah - Farida Yusuf; Nahrun Hartono; Nur Rifdah (System Information and Computer Technology (SYNCTECH), 2024)
The Selayar Islands Regency Education and Culture Office does not currently have a website to monitor school inventory data. This research aims to create a Information System that will help monitor school inventory under the supervision of the The Selayar Islands Regency Education and Culture Office. The research follows the waterfall method and uses experimental research with data collection through observation, interviews, and documentation. The application is tested using the black box testing method. The result is a school inventory monitoring application, and an evaluation conducted through questionnaires with 120 respondents shows a satisfaction rate of 82.26% for this application. It can be concluded that users are pleased with information system, and it is effective for monitoring school inventory at the Selayar Islands Regency Education and Culture Office.